Potential co-application of Burkholderia cepacia, calcium and chitosan on enhancement of storage life and quality of papaya fruits - Rahman, Md. Aminur; Abdul Rahman, Russly; Tengku Muda Mohamed, Mahmud; Kadir, Jugah; Begum, Most Mahbuba (Universiti Putra Malaysia Press, 2012)
The fruit of harvested papayas (cv. Sekaki), at colour stage two (mature-green with trace yellow), were treated with fungicide benocide® (0.33 gL-1) or with a combination of Burkholderia cepacia B23 (109 CFU mL-1) and 0.75% chitosan solution, amended with 3% calcium chloride and stored at 14 ± 0.5ºC and 90-95% RH for 28 d. The effectiveness of the treatments was assessed by evaluating their impacts on storability and changes in the quality attributes of fruits. Results indicated that fruit treated with the combination of B. cepacia B23-chitosan-CaCl2 showed delayed climacteric ethylene evolution and reduced respiration rate. The combined treatment reduced weight loss by more than 25% to the control. It also markedly slowed down the ripening of fruits, as shown by their retention of firmness 4.17 N after storage. Moreover, a delayed change in external colour and pH without compromising fruit quality was observed in the fruit receiving the combined treatment. The storage life was thus extended up to 15 d compared to the control. In addition, the incorporation of 3% CaCl2 into the combined treatment significantly increased the calcium content (81%) in the fruit compared to the control, resulting in the improved nutritional value of the papaya. This study provided an alternative method for fungicides treatment of papaya at post-harvest.